The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijms23168957
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and NLRP3-Inflammasome Inhibitory Activity of the Naturally Occurring Velutone F and of Its Non-Natural Regioisomeric Chalconoids

Abstract: Plant-derived remedies rich in chalcone-based compounds have been known for centuries in the treatment of specific diseases, and nowadays, the fascinating chalcone framework is considered a useful and, above all, abundant natural chemotype. Velutone F, a new chalconoid from Millettia velutina, exhibits a potent effect as an NLRP3-inflammasome inhibitor; the search for new natural/non-natural lead compounds as NLRP3 inhibitors is a current topical subject in medicinal chemistry. The details of our work toward t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…These results have indicated that the studied chalcones inhibit the canonical and non-canonical pathways of the NLRP3 inflammasome [ 264 ]. The naturally occurring chalcone veluton F and some of its regioisomers have also exhibited NLRP3 inflammasome inhibitory activity by inhibiting the release of IL-1β in both in vitro cell systems and in vivo animal models [ 265 ].…”
Section: Animal Studiesmentioning
confidence: 99%
“…These results have indicated that the studied chalcones inhibit the canonical and non-canonical pathways of the NLRP3 inflammasome [ 264 ]. The naturally occurring chalcone veluton F and some of its regioisomers have also exhibited NLRP3 inflammasome inhibitory activity by inhibiting the release of IL-1β in both in vitro cell systems and in vivo animal models [ 265 ].…”
Section: Animal Studiesmentioning
confidence: 99%
“…Compounds 6c , 7n , and 10 displayed low nanomolar potency in both models (Figure B). Of note, in THP-1 cells, the isoquinoline derivative 7n (IC 50 = 5.36 nM) and the tyrosine derivative 10 (IC 50 = 3.29 nM) were shown to be even more potent than the positive control MCC950 (IC 50 : 8.1 nM in human monocyte-derived macrophages as reported in ref ).…”
Section: Resultsmentioning
confidence: 99%
“…These findings prompted the development of potent and selective NLRP3 inhibitors that are extensively used as pharmacological tools to elucidate possible clinical applications of NLRP3 targeting strategies. , In this rapidly expanding research field, numerous compounds are already under preclinical investigation, and few of them have reached phase I/II clinical trials. Among these, MCC950 ( 1 , Figure ) is the most studied NLRP3 inhibitor after its early discovery in 2003 . MCC950 was shown to block canonical and noncanonical NLRP3 activation at nanomolar concentrations in vitro with high selectivity over AIM2, NLRC4, or NLRP1 inflammasomes .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, different NLRP3 in ammasome inhibitors have been reported to date, including the ones that directly inhibit the NLRP3 and those that act on its related signaling pathways [10]. Indeed, recently we identi ed a series of aryl sulfonamide derivatives (ASDs) and natural compounds with high potency and selectivity in inhibiting NLRP3 activation in vitro and in vivo [11,12]. Among all the cited inhibitors, nutraceutical compounds might be of high impact for their low side effects in prolonged treatments.…”
Section: Introductionmentioning
confidence: 99%